2023
DOI: 10.1002/aenm.202300086
|View full text |Cite
|
Sign up to set email alerts
|

Trace to the Source: Self‐Tuning of MOF Photocatalysts

Abstract: Benefitting from ultra‐high porosity, large specific surface area (SSA), and rich active sites, metal–organic frameworks (MOFs) have emerged as a star material in energy and environment related applications, especially in photocatalysis. In comparison with conventional photocatalysts, MOFs can be customized in terms of electronic structure, photo‐responsiveness, and morphological dimensions by rational design, which means that MOFs eliminate the need for other species to achieve enhanced photocatalytic perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 448 publications
0
10
0
Order By: Relevance
“…At present, many metal‐organic frameworks (MOFs) [ 81 ] and covalent organic frameworks (COFs) have been studied for photocatalytic CO 2 reduction. [ 82 ] Previous studies have shown that metal matrix nanocomposites derived from the destruction of MOF structures at high temperatures can be widely used as CO 2 RR photocatalysts.…”
Section: Application Of Sacs In Photocatalytic Co2 Reductionmentioning
confidence: 99%
“…At present, many metal‐organic frameworks (MOFs) [ 81 ] and covalent organic frameworks (COFs) have been studied for photocatalytic CO 2 reduction. [ 82 ] Previous studies have shown that metal matrix nanocomposites derived from the destruction of MOF structures at high temperatures can be widely used as CO 2 RR photocatalysts.…”
Section: Application Of Sacs In Photocatalytic Co2 Reductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), consisting of various structural connections of metal ions/clusters and distinct organic linkers through coordination bonding interactions, have been extensively used in countless application fields, such as gas adsorption, 6 photocatalysis, 7 and electrochemistry, 8 on account of their unique characteristics of structural diversity, tunable porosity, and designable functionality. Recent years have witnessed the outstanding discovery of semiconductor-like properties and excellent UV-light utilization performance of specific MOFs, thereby presenting their promising application prospects in photoactivated gas sensing.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, microporous metal–organic frameworks (MOFs) are formed by the self-assembly between metal cations and organic ligands and are deemed effective precursors or templates for OER catalysts. Due to their high specific surface area, large pore volume, and adjustable pore size, MOF materials and their derivatives have immense potential in gas storage and separation, , host–guest recognition, , electro/photocatalysis, and more. As the coordination environments of different metals may be similar within isostructures, it is highly possible to rationally design and synthesize multimetal MOFs. Furthermore, different metal sites in MOFs can exhibit different functions through appropriate treatment, enabling them to transform into highly active and stable catalytic nanomaterials. In recent years, there has been extensive research on MOF-derived transition metal species, which are considered to be ideal OER catalysts that can replace noble metal catalysts. Different types of metal derivatives play a crucial role, such as MOF-derived metal sulfides, nitrides, , selenides, phosphates, and hydroxides, which ensure effective resorption and desorption of reaction intermediates during catalysis, thereby reducing the energy required for OER reactions.…”
Section: Introductionmentioning
confidence: 99%